2021
DOI: 10.5812/asjsm.107042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TRX Suspension Training on Proprioception and Muscle Strength in Female Athletes with Functional Ankle Instability

Abstract: Background: Functional ankle instability (FAI) is a common consequence of ankle sprain injury, especially in high-impact sports. Objectives: To investigate the effect of six weeks of suspension training with total resistance exercises (TRX) on proprioception and muscle strength in female athletes with FAI. Methods: Thirty female athletes with FAI (age: 21.9 ± 2.2 years, height: 169.3 ± 4.2 cm, and weight: 59.8 ± 6.1 kg) were randomly assigned to two equally numbered groups: TRX training and controls based on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…El TRX, como método y equipamiento innovador que se está empezando a utilizar en las clases de EF, posibilita la ejecución de ejercicios utilizando la resistencia del propio cuerpo permitiendo trabajar en condiciones de inestabilidad, tanto de forma unilateral como bilateral, donde la dificultad puede ajustarse al modificar el ángulo del cuerpo en relación con el suelo (Demirarar et al, 2021). Los beneficios del uso del TRX se relacionan con: la mejora de la composición corporal, fuerza y resistencia muscular, y el equilibrio en atletas preadolescentes (Fayazmilani et al, 2022), mayor propiocepción y fuerza muscular en chicas atletas con inestabilidad de tobillo (Khorjahani et al, 2021), mejoras en el salto vertical en jóvenes jugadores de baloncesto (Demirarar et al, 2021) y mejoras en la flexibilidad en jóvenes judokas (Norambuena et al, 2021). Sin embargo, hay escasa evidencia científica sobre su uso en el ámbito educativo.…”
Section: Introductionunclassified
“…El TRX, como método y equipamiento innovador que se está empezando a utilizar en las clases de EF, posibilita la ejecución de ejercicios utilizando la resistencia del propio cuerpo permitiendo trabajar en condiciones de inestabilidad, tanto de forma unilateral como bilateral, donde la dificultad puede ajustarse al modificar el ángulo del cuerpo en relación con el suelo (Demirarar et al, 2021). Los beneficios del uso del TRX se relacionan con: la mejora de la composición corporal, fuerza y resistencia muscular, y el equilibrio en atletas preadolescentes (Fayazmilani et al, 2022), mayor propiocepción y fuerza muscular en chicas atletas con inestabilidad de tobillo (Khorjahani et al, 2021), mejoras en el salto vertical en jóvenes jugadores de baloncesto (Demirarar et al, 2021) y mejoras en la flexibilidad en jóvenes judokas (Norambuena et al, 2021). Sin embargo, hay escasa evidencia científica sobre su uso en el ámbito educativo.…”
Section: Introductionunclassified
“…A significant contribution is made by the proprioceptive information acquired from the receptors in the joints and muscles [6]. Proprioceptive information from the ankle muscles is important [7]. The ankle proprioception is impaired in individuals with ankle sprains, contributing to the development and maintenance of chronic ankle instability (CAI) [8].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, leads to alterations in muscle contraction through reflex muscle activity and the activation of muscle spindles [ 6 ]. Studies have shown that higher vibration frequencies (35–45 Hz) used in conjunction with attachment cords for static and dynamic exercises significantly increase muscle activation compared to lower frequencies (35 Hz) [ 7 , 8 ]. TVT is a sophisticated form of resistance training that does not rely on traditional weights.…”
Section: Introductionmentioning
confidence: 99%